Information and Communication Technology in Ugandan Higher Education. - John Michael, Edoru; Adebayo, Sanni T. (Kabale University, 2019)
This article focuses on the use of Information and Communications Technology (ICT) as a strategy for delivering effective management of educational services in a cross-section of institutions of higher learning. Makerere University in Uganda is taken as a case study where ICT was introduced with the main aim of improving effectiveness in the delivery of educational services. ICT has become a tool of great importance in today’s business in all spheres of life globally. From commerce to aeronautics, medicine and education, the daily use of ICT is vital to the success of business. In the area of higher education management, ICT use is of central significance since universities of the contemporary world cannot afford to ignore the role that ICT plays in the running of their institutions as a business. As a matter of necessity, universities are therefore required to embrace ICT adoption in teaching/learning and administrative activities. This study discusses the concept of ICT, perceptions of stakeholders in the effectiveness of ICT adoption, educational services management and ICT, as well as strategies for effective ICT use in educational services management.